# Question and Answers Forum

Integration Questions

Question Number 115781 by bemath last updated on 28/Sep/20

$$\underset{\mathrm{0}} {\overset{\frac{\mathrm{1}}{\:\sqrt{\mathrm{2}}}} {\int}}\:\frac{{x}\:\mathrm{sin}^{−\mathrm{1}} \left({x}^{\mathrm{2}} \right)}{\:\sqrt{\mathrm{1}−{x}^{\mathrm{4}} }}\:{dx}\:=? \\$$ $$\int\mathrm{2}^{−{x}} \:\mathrm{tanh}\:\left(\mathrm{2}^{\mathrm{1}−{x}} \right)\:{dx}\:=? \\$$

Answered by bobhans last updated on 28/Sep/20

$${I}=\underset{\mathrm{0}} {\overset{\frac{\mathrm{1}}{\:\sqrt{\mathrm{2}}}} {\int}}\:\frac{{x}.\mathrm{sin}^{−\mathrm{1}} \left({x}^{\mathrm{2}} \right)}{\:\sqrt{\mathrm{1}−{x}^{\mathrm{4}} }}\:{dx} \\$$ $${let}\:{u}\:=\:\mathrm{sin}^{−\mathrm{1}} \left({x}^{\mathrm{2}} \right)\:\rightarrow\begin{cases}{{x}=\frac{\mathrm{1}}{\:\sqrt{\mathrm{2}}}\:\rightarrow{u}=\frac{\pi}{\mathrm{6}}}\\{{x}=\mathrm{0}\rightarrow{u}=\mathrm{0}}\end{cases} \\$$ $${I}=\underset{\mathrm{0}} {\overset{\frac{\pi}{\mathrm{6}}} {\int}}\:\frac{\mathrm{1}}{\mathrm{2}}{u}\:{du}\:=\:\left[\:\frac{\mathrm{1}}{\mathrm{4}}{u}^{\mathrm{2}} \:\right]_{\mathrm{0}} ^{\frac{\pi}{\mathrm{6}}} \\$$ $$=\:\frac{\mathrm{1}}{\mathrm{4}}×\frac{\pi^{\mathrm{2}} }{\mathrm{36}}\:=\:\frac{\pi^{\mathrm{2}} }{\mathrm{144}} \\$$

Answered by Dwaipayan Shikari last updated on 28/Sep/20

$$\int_{\mathrm{0}} ^{\frac{\mathrm{1}}{\:\sqrt{\mathrm{2}}}} \frac{\mathrm{xsin}^{−\mathrm{1}} \left(\mathrm{x}^{\mathrm{2}} \right)}{\:\sqrt{\mathrm{1}−\mathrm{x}^{\mathrm{4}} }}\mathrm{dx} \\$$ $$\frac{\mathrm{1}}{\mathrm{2}}\int_{\mathrm{0}} ^{\frac{\mathrm{1}}{\mathrm{2}}} \frac{\mathrm{sin}^{−\mathrm{1}} \left(\mathrm{t}\right)}{\:\sqrt{\mathrm{1}−\mathrm{t}^{\mathrm{2}} }}\mathrm{dt} \\$$ $$\frac{\mathrm{1}}{\mathrm{4}}\left[\left(\mathrm{sin}^{−\mathrm{1}} \left(\mathrm{t}\right)\right)^{\mathrm{2}} \right]_{\mathrm{0}} ^{\frac{\mathrm{1}}{\mathrm{2}}} =\frac{\mathrm{1}}{\mathrm{4}}.\left(\frac{\pi}{\mathrm{6}}\right)^{\mathrm{2}} =\frac{\pi^{\mathrm{2}} }{\mathrm{144}} \\$$

Answered by mathmax by abdo last updated on 28/Sep/20

$$\mathrm{changement}\:\mathrm{arcsin}\left(\mathrm{x}^{\mathrm{2}} \right)=\mathrm{t}\:\:\mathrm{give}\:\mathrm{x}^{\mathrm{2}} \:=\mathrm{sint}\:\Rightarrow\mathrm{x}\:=\sqrt{\mathrm{sint}}\:\Rightarrow \\$$ $$\int_{\mathrm{0}} ^{\frac{\mathrm{1}}{\sqrt{\mathrm{2}}}} \:\:\frac{\mathrm{xarcsin}\left(\mathrm{x}^{\mathrm{2}} \right)}{\sqrt{\mathrm{1}−\mathrm{x}^{\mathrm{4}} }}\mathrm{dx}\:=\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{6}}} \:\frac{\mathrm{t}\sqrt{\mathrm{sint}}}{\sqrt{\mathrm{1}−\mathrm{sin}^{\mathrm{2}} \mathrm{t}}}×\frac{\mathrm{cost}}{\mathrm{2}\sqrt{\mathrm{sint}}}\:\mathrm{dt} \\$$ $$=\frac{\mathrm{1}}{\mathrm{2}}\:\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{6}}} \:\mathrm{tdt}\:=\frac{\mathrm{1}}{\mathrm{2}}\left[\frac{\mathrm{t}^{\mathrm{2}} }{\mathrm{2}}\right]_{\mathrm{0}} ^{\frac{\pi}{\mathrm{6}}} \:=\frac{\mathrm{1}}{\mathrm{4}}×\frac{\pi^{\mathrm{2}} }{\mathrm{36}}\:=\frac{\pi^{\mathrm{2}} }{\mathrm{144}} \\$$

Answered by Ar Brandon last updated on 28/Sep/20

$$\mathcal{I}=\int\mathrm{2}^{−{x}} \mathrm{tanh}\left(\mathrm{2}^{\mathrm{1}−{x}} \right)\mathrm{d}{x}=−\frac{\mathrm{1}}{\mathrm{2ln2}}\int−\mathrm{2}^{\mathrm{1}−{x}} \mathrm{ln2tanh}\left(\mathrm{2}^{\mathrm{1}−{x}} \right)\mathrm{d}{x} \\$$ $$\:\:\:=−\frac{\mathrm{1}}{\mathrm{2ln2}}\int\mathrm{tanh}\left(\mathrm{u}\right)\mathrm{du}\:\:\:\:\:\:\:\:\:\:\:\left\{\frac{\mathrm{d}}{\mathrm{d}{x}}\left(\mathrm{2}^{\mathrm{1}−{x}} \right)=−\mathrm{2}^{\mathrm{1}−{x}} \mathrm{ln2}\right\} \\$$ $$\:\:\:=−\frac{\mathrm{1}}{\mathrm{2ln2}}\left\{\mathrm{utanh}\left(\mathrm{u}\right)−\int\frac{\mathrm{u}}{\mathrm{1}−\mathrm{u}^{\mathrm{2}} }\mathrm{du}\right\} \\$$ $$\:\:\:=−\frac{\mathrm{1}}{\mathrm{2ln2}}\left\{\mathrm{utanh}\left(\mathrm{u}\right)+\frac{\mathrm{ln}\mid\mathrm{1}−\mathrm{u}^{\mathrm{2}} \mid}{\mathrm{2}}\right\}+\mathcal{C} \\$$ $$\:\:\:=−\frac{\mathrm{1}}{\mathrm{2ln2}}\left\{\mathrm{2}^{\mathrm{1}−{x}} \mathrm{tanh}\left(\mathrm{2}^{\mathrm{1}−{x}} \right)+\frac{\mathrm{ln}\mid\mathrm{1}−\mathrm{2}^{\mathrm{2}\left(\mathrm{1}−{x}\right)} \mid}{\mathrm{2}}\right\}+\mathcal{C} \\$$